Strategi Penguatan Literasi Digital untuk Meningkatkan Kesiapan dan Daya Saing Lulusan Sekolah Menengah dalam Ekosistem Kerja Digital - Herlina; Sulistianingsih; Putri, Arbiana; Arifannisa; Masrum, Masrum (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The development of the digital work ecosystem demands that secondary school graduates possess digital literacy skills that go beyond the mere use of technological devices, encompassing critical thinking, digital communication, and ethical awareness in cyberspace. This study aims to examine relevant strategies for strengthening digital literacy to enhance the readiness and competitiveness of secondary school graduates in the digital workforce era. The research method used a qualitative approach with a literature review design, where data was obtained from Google Scholar and other credible sources such as ResearchGate, ScienceDirect, Wiley Online Library, and SpringerLink as many as 50 articles published between 1997 and 2025, then rigorously selected to obtain 34 articles that were further analyzed using descriptive analysis techniques. The findings reveal that effective digital literacy enhancement strategies include the integration of Digital Literacy Theory, 21st Century Skills, and the TPACK framework into the curriculum, digital project-based learning, teacher capacity building, and equitable infrastructure provision. Case studies of national programs such as the Digital Talent Scholarship also highlight the success of practical training approaches in improving students' digital workforce competencies.